Adaptable Automation Interface for Multi-Unmanned Aerial Systems Control: Preliminary Usability Evaluation. (September 2013) - Calhoun, Gloria; Draper, Mark; Miller, Christopher; Ruff, Heath; Breeden, Chad; Hamell, Joshua
With advances in automation technologies, systems are now being considered wherein a single operator supervises multiple unmanned aerial vehicles. Supervisory control of highly autonomous systems will require a new interface design. The present effort extends a delegation control concept to enable a pilot to flexibly change the role of automation during the course of a mission, seamlessly transitioning between four different control modes ranging from manual (pilot controls the vehicle's flight with stick and throttle control) to high level "plays" (pilot's command initiates a series of automated tasks). This novel concept was instantiated into a dynamic laptop simulation to support a usability evaluation in which participants employed the multi-level control architecture during ninety minute sessions. Data include comments recorded with a think-aloud paradigm and questionnaire responses. Results indicated that this adaptable pilot-automation interface for multi-unmanned systems control is promising. The findings include perspectives from both pilot and gamer participants that will help advance design of multi-level control for future aviation systems.